Manajemen Pendidikan Sekolah Menengah Atas/Sekolah Menengah Kejuruan di Provinsi Nusa Tenggara Timur (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2020)
The purpose of this study is to analyze the management of personnel of SMA/ SMK teachers in East Nusa Tenggara Province. This study uses a qualitative description that will produce descriptive information about the management of high school / vocational teacher personnel in East Nusa Tenggara Province. Data collection techniques with in-depth interview focus discussion groups (FGD), documentary studies and online data search. This study uses management theory which include planning, organization, actuating and controlling. The results of the study showed that the planning had not recorded the distribution of teachers not evenly distributed, the Provincial Education Service Organization was too large and the existence of UPTs in NTT districts/cities had not carried out their duties and functions optimally, the motivation of teachers was quite high despite not having received incentives, especially honorary teachers/committees, functions supervision is still limited in both quantity and quality.